Cognitive Function and Army Rejection Rate in Young Adult Male Offspring of Women With Diabetes: A Danish population-based cohort study - Nielsen, Gunnar Lauge; Dethlefsen, Claus; Sørensen, Henrik Toft; Pedersen, Jan Fog; Molsted-Pedersen, Lars (Diabetes care, 2007)
OBJECTIVE:--While maternal diabetes is a known risk factor for perinatal complications, there is little data on long-term intellectual outcome in offspring. We compare the rejection rate and cognitive functioning of military conscripts according to maternal diabetes status during pregnancy. RESEARCH DESIGN AND METHODS--We identified a cohort of Danish male offspring of diabetic mothers born between 1976 and 1984 and followed this cohort together with population-based control subjects to military conscription. The main outcome was army rejection rate and cognitive function measured with a validated intelligence test. RESULTS:--The army rejection rate was 52.5% among 282 men whose mothers had diabetes during pregnancy and 45.4% among 870 control subjects (risk difference 7.3 [95% CI 0.6-14.0]). Mean cognitive scores were 41.4 units (95% CI 40.2-42.6) in diabetes-exposed conscripts and 42.7 units (42.0-43.4) in control subjects. Stratification by gestational age, Apgar score, and White's class (A-F) did not change the associations. In a subgroup analysis using available data on A1C levels during pregnancy, this variable was inversely associated with cognitive functioning. In men with maternal A1C <7%, cognitive scores were identical to those in control subjects. CONCLUSIONS:--The slightly higher army rejection rate in men with maternal diabetes indicates higher morbidity. The identical cognitive functioning in cases of well-controlled maternal diabetes compared with that in control subjects is reassuring, but the negative association between A1C and cognitive score highlights the importance of striving for optimal metabolic control in diabetic women who are or plan to become pregnant.